Prevalence of depression in Europe using two different PHQ-8 scoring methods. (1st June 2022) - Arias De La Torre, J.; Vilagut, G.; Ronaldson, A.; Serrano-Blanco, A.; Valderas, J.; Martín, V.; Dregan, A.; Bakolis, I.; Alonso, J.
Abstract : Introduction: The prevalence of depression based on the Patient Health Questionnaire-8 (PHQ-8) may vary depending on the scoring method. Objectives: 1) To describe the prevalence of depression in Europe using two PHQ-8 scoring methods. 2) To identify the countries with the highest prevalence according to each method. Methods: Data from 27 countries included in the European Health Survey (EHIS-2) for the year 2014/2015 were used (n=258, 888). All participants who completed the PHQ-8 were included. The prevalence of depression and its 95% Confidence Interval (95%CI) were calculated overall for the whole of Europe and for each country using a PHQ-8≥10 cut-off point and the PHQ-8 algorithm scoring method. Weights derived from the complex sample design were considered for their calculation. Results: The overall prevalence of depression for all Europe was lower using the PHQ-8>=10 cut-off point (6.38%, 95%CI 6.24-6.52) than the PHQ-8 algorithm (7.01%, 95%CI, 6.86-7.16). Using the PHQ-8≥10 cut-off point, the highest prevalence was observed in Iceland (10.33%, 95%CI, 9.33-11.32), Luxembourg (9.74%, 95%CI, 8.76-10.72) and Germany (9.24%, 95%CI, 8.82-9.66). Using the PHQ-8 algorithm the highest rates were observed in Hungary (10.99%, 95%CI, 10.14-11.84), Portugal (10.63%, 95%CI, 9.96-11.29) and Iceland (9.80%, 95%CI, 8.77-10.83). Conclusions: There is variability in the prevalence of depression rates in Europe according to the PHQ-8 scoring method. These findings suggest the necessity of identify the method of choice for each country comparing with a gold standard measure (clinical diagnosis). Countries with consistent higher prevalence of depression based on PHQ-8 regardless of scoring method deserve further study. Disclosure: This work has been funded by CIBERESP (ESP21PI05)